Grid-Based remotely sensed hydrodynamic surface runoff model using emissivity coefficient / Jurina Jaafar - Jaafar, Jurina (Institute of Graduate Studies, UiTM, 2016)
The development of a hydrodynamic distributed model is designed to simulate discharge and water levels as a function of space and time. The development of the model strongly depends on the physical based parameters, examples of physical parameters that include roughness Manning’s n, hydraulic conductivity, soil depth, river geometry and the surface land cover. Most Malaysian catchments are not gauged, albeit or scarce discharge data is available and the difficulty to access and hard to obtain in situ site area information. These scenarios have brought an interest into this study to use satellite images in obtaining information of the ground surface from inference in a digital elevation model (DEM) and other information such as the land use characteristics. The processes of infiltration and overland runoff flows are complex phenomenon. Both interact on the soil surface on the ground at its own capacity. Since soil surface is the primary order that control the hydrological and hydraulic processes, the topographic of the land use sensed by the satellite is used to describe the spatial variations of the ground surface. In this study, a quantitative surface runoff estimation using the information of emissivity from the remotely sensing technique is developed for potential input representing the surface roughness. The process from the satellite information allows an optimal judgment to decide the most appropriate Manning roughness to be used in the simulation of surface runoff...